Filosofi Perkawinan Campur Budaya Lokal Masyarakat Jogja Perspektif Hukum Islam dan Kearifan Lokal - Yudi Surono (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
Intermarriage is a complex and meaningful social phenomenon in a multicultural society such as Yogyakarta. Amidst the plurality of cultures and beliefs, this practice not only touches the personal realm, but also involves the dynamics of Islamic law and local wisdom. This study aims to examine in depth how Javanese cultural philosophy, local values, and religious norms interact in the practice of intermarriage, and how society bridges the potential conflict between normative law and social reality. With a qualitative approach and descriptive-analytical methods, this study combines normative studies of Islamic legal sources with empirical exploration through in-depth interviews, participatory observation, and cultural literature studies. The results of the study indicate that values ​​such as harmony (rukun), tepo seliro (tolerance), and gotong royong (mutual cooperation) are the social foundations in building acceptance of differences in identity in intermarriage. These findings underline the importance of a contextual and integrative approach in understanding Islamic law in a dynamic social space, as well as providing theoretical contributions to the development of a legal paradigm based on local wisdom. This study emphasizes that synergy between religious norms and local culture is not only possible, but also inevitable in building an inclusive and just society.